POTRET MUATAN EDUCATION FOR SUSTAINABLE DEVELOPMENT DALAM BUKU AJAR IPA SMP KELAS IX BERDASARKAN TIGA PILAR DAN LIMA KOMPONEN ESD TILBURY & WORTMAN - Aprillia, Dian Norma; Suriswo, Suriswo; Tity Kusrina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Education for Sustainable Development (ESD) is essential for preparing learners to address environmental, social, and economic challenges. This study examines the integration of ESD content in a Grade IX junior secondary school science textbook under the Merdeka Curriculum. Using qualitative content analysis, narrative texts, illustrations, tables, and learning activities were analyzed based on three sustainability pillars and five ESD components proposed by Tilbury and Wortman. The results show that ESD is present but unevenly integrated, with an average score of 5.2 out of 10. Environmental and social pillars are more dominant than the economic pillar. Critical and future-oriented thinking is emphasized, while participation, decision-making, and systemic approaches remain limited. These findings indicate that ESD integration is still partial and requires strengthening to support sustainability competencies and SDG 4.7. Keywords: education for sustainable development, science textbook, Merdeka Curriculum